Single-dose pharmacokinetics of delavirdine mesylate and didanosine in patients with human immunodeficiency virus infection. - Morse, G D (1997)
Delavirdine is a nonnucleoside reverse transcriptase inhibitor with in vitro activity against human immunodeficiency virus type 1 (HIV-1) that is currently being evaluated in combination regimens with various nucleoside analogs, including didanosine. Due to the pH-dependent solubility of delavirdine, the buffering agents in didanosine formulations may reduce delavirdine absorption. To evaluate the potential interaction between these agents, 12 HIV-infected patients (mean [+/- standard deviation] CD4+ cell count, 304 +/- 213/mm3) were enrolled in a three-way crossover single-dose study. Didanosine (125 to 200 mg given as buffered tablets) and delavirdine mesylate (400 mg) pharmacokinetics were evaluated when each drug was given alone (treatments A and B, respectively), when the two drugs were given concurrently (treatment C), and when didanosine was given 1 h after delavirdine (treatment D). Delavirdine exposure was reduced by concurrent administration of didanosine. The maximum drug concentration in serum (Cmax) was reduced from 7.22 +/- 4.0 to 3.51 +/- 1.9 microM, and the area under the concentration-time curve from 0 h to infinity (AUC0-->infinity) was reduced from 22.5 +/- 14 to 14 +/- 5.7 microM.h. The extent of N-dealkylation, as indicated by the ratio of the N-dealkylated delavirdine AUC0-->infinity to the delavirdine AUC0-->infinity, was unchanged across study treatments (P = 0.708). Reductions in didanosine exposure were observed during concurrent administration with delavirdine with a Cmax reduction from 4.65 +/- 2.0 to 3.22 +/- 0.59 microM and an AUC0-->infinity reduction from 7.93 +/- 3.9 to 6.54 +/- 2.3 microM.h. Thus, concurrent administration of delavirdine and didanosine may reduce the AUC0-->infinity of both drugs, although the clinical significance of this reduction is unknown. Administration of delavirdine 1 h before didanosine avoided the interaction. Due to the single-dose nature of this study, these findings require further evaluation at steady state.